Corporate Social Responsibility in Indonesia: A Bibliography Analysis - Wuryan Andayani; Iqbal Lhutfi; Melinda Ibrahim; Kartika Putri Kumalasari; I Wayan Pradnyantha Wirasedana; M. Iswahyudi; Retno Wulandari (Jurnal Pendidikan Akuntansi & Keuangan, 2023)
This study uses a bibliographical approach to summarize research on the topic of corporate social responsibility (CSR) in Indonesia from 2007 to 2022. The research was conducted using articles published on the SINTA index. The 20 articles analyzed were summarized based on regulatory design themes, strategic perspectives, models and stakeholders. In this study it was found that the design of regulatory practices regarding CSR is necessary in obtaining legal legitimacy. Furthermore, the perspective of CSR strategy among listed companies in Indonesia is limited to donation and community development activities, and there has been little improvement in CSR implementation. In its implementation, CSR is still mostly at the charity stage. The success of CSR implementation is largely determined by the company's willingness and awareness. The information disclosed is more quantitative than qualitative.